(untitled) (Mongolian Journal of Agricultural Sciences, 2018)
The nanocrystal, phase transformation and microstructure behavior of Ni50Ti50 shape memory alloy was investigated by scanning electronic microscope, X-ray diffraction and differential scanning calorimetry. The results showed that the microstructure of Ni-Ti binary alloy consists of the NiTi2 phase and the NiTi matrix phase. One-step phase transformation was observed alloy.